SHIFTING SOCIO-RELIGIOUS VALUES IN THE PRACTICE OF SINGLE-MARGA MARRIAGE: A CASE STUDY IN BUNUT VILLAGE, TORGAMBA DISTRICT, SOUTH LABUHANBATU REGENCY - Harahap, Sutan Maradoli; Irwansyah, Irwansyah (Pena Cendekia Insani, 2025)
This study examines the shift in socio-religious values in the practice of same-clan marriage in Bunut Village, Torgamba Subdistrict. Traditionally, such marriages were considered taboo due to their violation of Mandailing customary norms, which uphold the principle of *partuturon* (lineage). However, over time and with the growing influence of religion and the changing perspectives of the younger generation, this prohibition has become more relaxed. Factors such as education, social environment, and a more inclusive religious understanding have influenced the community in reinterpreting customary rules once seen as absolute. This research uses a descriptive qualitative method with a phenomenological approach, conducted through fieldwork in Bunut Village, Torgamba. Data were collected through interviews, observations, and documentation, with validity ensured through source triangulation. Analysis was carried out through data reduction, thematic presentation, and conclusion drawing to understand the shift in customary and religious values in the practice of same-clan marriage. The findings show that the practice of same-clan marriage in Bunut Village has undergone a significant socio-religious value shift. Customary prohibitions, once viewed as sacred, are now interpreted more loosely, especially by the younger generation who are more educated, information-literate, and possess a contextual religious perspective. Custom is no longer an absolute boundary in choosing a partner, but rather a relative consideration. Marital harmony, love, and religious legitimacy have become the primary priorities. This transformation reflects the emergence of a new social reality that is more rational, adaptive, and flexible in response to contemporary change.